Budaya organisasi sebagai penguat hubungan antara kepuasan kerja dan kinerja pegawai - Arwinsyah Arwinsyah; Samdin Samdin; Mahmudin A. Sabilalo (Universitas Kristen Maranatha, 2025)
The Bahteramas Regional Public Hospital (RSUD Bahteramas), as a government-owned institution, is responsible for providing optimal services to the public as service users. In managing its human resources to achieve effective and efficient employee performance, the hospital requires organizational synergy that can affect the successful attainment of its vision and mission, particularly as a healthcare institution. The primary objective of this research is to investigate and evaluate the impact of job satisfaction on employee performance, with organizational culture serving as a mediating variable. This research employs a quantitative method and utilizes the convenience sampling approach for participant selection, and 71 employees of RSUD Bahteramas, Southeast Sulawesi Province, were selected as respondents through a questionnaire survey. The data were examined through Partial Least Squares-Structural Equation Modeling. Findings revealed that job satisfaction does not have a significant implication on employee performance. In contrast, organizational culture emerges as a strong positive determinant, exerting a meaningful and statistically significant impact on employee performance. On the other hand, organizational culture can strengthen in mediating the linkage between employee job satisfaction and their performance outcomes. In theoretical terms, the results of this study expand the understanding of the relationship between job satisfaction, organizational culture, and employee performance within the context of human resource management. In practical terms, the findings provide guidance for hospital management in formulating strategies and policies that foster a productive and positive work environment. Conceptually, this research is grounded in theories of job satisfaction, organizational culture, and employee performance, emphasizing the importance of internal factors in influencing individual performance within an organization.